Fusible glass and its uses

By designing lead-free fusible glass, including SiO2 and low Al2O3, the alkali metal oxide ratio is optimized, and the problems of high lead content and insufficient stability in sensor applications are solved, achieving high time, thermal stability and chemical stability without Lead fusible glass.

CN113461327BActive Publication Date: 2024-12-24SCHOTT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110319626.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-25
Publication Date
2024-12-24
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

In the prior art, fusible glass with low softening temperature has problems such as high lead content and unstable and difficult to replace in sensor applications, and lead-free fusible glass has insufficient chemical stability under fluctuating environmental conditions.

Method used

A lead-free fusible glass is designed, which contains SiO2 and Al2O3 below 2 wt%, with a linear thermal expansion coefficient greater than 10*10-6/K, a dielectric constant between 7.10 and 7.80, and a glass transition temperature of 400°C. to 550°C and ensure their time and thermal stability in harsh environments by optimizing the proportion of alkali metal oxides and other components.

Benefits of technology

High time and thermal stability of lead-free fusible glass used in sensor applications is achieved, avoiding the harmful effects of lead and maintaining good chemical and dielectric properties in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113461327B_ABST
    Figure CN113461327B_ABST
Patent Text Reader

Abstract

The present invention relates generally to glass materials, in particular fusible glass, and uses thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates generally to glass materials, in particular fusible glass, and uses thereof. Background Art

[0002] Fusible glass is generally a glass or glass material with a low softening temperature, especially for establishing a seal, such as a sealed connection between two joints. Fusible glass can be in the form of a glass body in particular, wherein two or more glass bodies made of this fusible glass are fused to each other. For example, a wire or lead (generally a metal material) and alternatively and / or additionally a ceramic material can be present between the initial glass bodies or at least contact the initial glass, and then surrounded by the fusible glass after heat treatment, in this way, it is protected from environmental and other influences. However, fusible glass can also be in the form of glass powder, which can be used to establish a connection in a process similar to, for example, tin soldering. The connection established by means of this fusible glass is generally extremely mechanically stable, and is highly impermeable, for example, to the passage of fluids. In particular, this connection can even be designed as an airtight seal or a vacuum seal. Based on these favorable properties of fusible glass, they can also be used for extremely strict applications, for example, in the field of sensors such as pressure sensors. Especially in the field of sensors (e.g. pressure sensors), in addition to the melting behavior (e.g. low softening temperature), of particular importance are the dielectric properties of the glass (such as the dielectric constant) and its thermal and / or temporal stability and generally the stability of the glass with respect to environmental influences (e.g. humidity and / or temperature fluctuations).

[0003] Fusible glasses with particularly low softening temperatures (in the range of 350° C. to 700° C.) often contain lead, since lead oxide is a component that reduces the softening temperature but still ensures the stability of the glass with respect to environmental influences. In particular, the lead content in fusible glasses or solder glasses also ensures that the dielectric properties are sufficiently stable for sensor applications while ensuring a sufficiently low softening temperature. However, lead is a known hazardous substance, so it is desirable to replace lead-containing fusible glasses and solder glasses from a health, regulatory and environmental perspective.

[0004] For example, a reduction in the softening temperature of the glass can be achieved by replacing lead with a high content of alkali metal oxides as a glass component. However, against the background of the stability of the material properties of the glass under fluctuating environmental conditions, such fluctuations can occur, for example, when the conditions of use of sensors such as pressure sensors change, alkali metal oxides present problems, especially with regard to the dielectric properties. Therefore, the content of alkali metal oxides is limited, so that a sufficiently low softening temperature cannot be set by increasing the alkali metal content.

[0005] Japanese patent application JP 2016 / 074575 A describes optical glasses with low linear thermal expansion coefficients that can be used for precision molding. The application does not describe, for example, -6 / K high thermal expansion coefficient fusible glass.

[0006] Japanese patent application JP 2002 / 167234A describes a fusible glass which can be used to establish a vacuum-tight connection in a metal container such as a thermos flask. The glass is lead-free and has a boron oxide content of up to 37 mol % and an SiO2 content of only up to 45 mol %. Such glasses generally have only very low chemical resistance. In particular, the resistance of such composite glasses is quite low.

[0007] US patent application US 2002 / 0001881 A1 describes lead-free glass and glass tubes for encapsulating semiconductor materials, with a thermal expansion coefficient of up to 10.5*10 -6 / K, at a temperature not exceeding 710°C, the glass viscosity is 10 6 dPas. To ensure that the glass has sufficient chemical stability, the minimum Al2O3 content of the glass according to the example of US 2002 / 0001881 A1 is 2.5 wt%. After melting, the glass forms a tube, the end of which can melt under the action of heat. The application does not describe fusible glasses or solder glasses for sensor applications.

[0008] US patent application US 2003 / 0050173 A1 describes silicate compositions of optical glasses which can be used as substrates for optical thin film interference filters. This application does not describe fusible glasses.

[0009] US patent application US 2003 / 0094013 A1 relates to a pressable glass, one form of which exhibits only slight adhesion. This application does not describe fusible glasses or solder glasses.

[0010] US patent application US 2003 / 0161048 A1 relates to a planar lens having a flat glass substrate in which a component increasing the refractive index is diffused. This application does not describe fusible glass or solder glass.

[0011] Japanese patent application JP 2003 / 351024 A describes a pressable glass which does not melt onto the mould surface during pressing. This application does not describe fusible glasses or solder glasses.

[0012] US patent application US 2006 / 0063009 A1 describes high-strength glass, for example for flat panel displays. The glass contains at least one rare earth oxide and can be subjected to a tempering process. However, US 2006 / 0036009 A1 does not describe the composition of fusible glass or solder glass.

[0013] Japanese patent application JP 2008 / 189546 A also describes a pressable glass which does not melt onto the mould surface during pressing. This application does not describe fusible glasses or solder glasses.

[0014] Japanese patent application JP 2010 / 083723A relates to optical glass, sample holder and optical element for improving image quality during observation, image acquisition and measurement accuracy during measurement. The application does not mention fusible glass or solder glass.

[0015] Japanese patent application JP 2011 / 068507 A describes providing spherical multicomponent glass particles as sintering aids in ceramic production. Fusible glasses or solder glasses are not described in this application.

[0016] US patent application US 2011 / 0165380 A1 relates to a cover plate device for an electronic display device such as a liquid crystal display. It comprises an aluminosilicate glass which can be chemically toughened, for example. Fusible glass or solder glass is not described in this application.

[0017] International patent application WO 2013 / 018586 A1 describes an optical glass having a glass transition temperature below 600°C and having specific optical constants (such as refractive index and Abbe number) that contains fewer rare earth elements than known glasses with corresponding optical constants. The glass can also be used to make packages for LEDs or camera lenses. The application does not mention sensor applications.

[0018] Japanese patent application JP 2014 / 234341 A relates to a high-strength glass element made of sintered glass powder and having an ion exchange layer on the glass surface. Fusible glass or solder glass is not described in this application.

[0019] Japanese patent application JP 2017 / 193464 A relates to optical glass. Fusible glass or solder glass is not described in this application. Summary of the invention

[0020] In view of this, there is a need for lead-free fusible glasses with low softening temperatures which still have sufficient temporal and / or thermal stability of material properties under the conditions of use for sensor applications.

[0021] An object of the present invention is to provide a glass which at least partially overcomes or alleviates the deficiencies in the prior art.

[0022] The solution of the invention for achieving the above-mentioned objects is the subject of the independent claims. Particular and preferred embodiments can be found in the dependent claims.

[0023] The present invention relates to a fusible glass comprising SiO2 and less than 2 wt% Al2O3, wherein the linear thermal expansion coefficient of the fusible glass is 20-300 Greater than 10*10 -6 / K, and wherein the fusible glass contains no PbO except for unavoidable traces. The dielectric constant ε of the fusible glass, preferably determined at a measuring frequency of 1 MHz and a temperature of 25°C, is r Preferably, the glass transition temperature T g The temperature is 400°C to 550°C, preferably 450°C to 500°C.

[0024] This fusible glass design offers a number of advantages.

[0025] The invention also relates to the use of the fusible glass according to the embodiments as a pressed or molded article for liquid-tight and gas-tight insulation of wires and ceramic components in a metal shell (for example a steel variant), wherein the average CTE of the entire component is about 10-12*10 -6 / K. These components are components of pressure sensors / gas sensors or other sensors and can be used even under harsh environmental conditions. Although the melting temperature of the fusible glass according to the embodiment is higher than the melting temperature of known lead-containing solder glasses and fusible glasses, the fusible glass according to the embodiment has excellent crystallization stability, which is particularly beneficial for solder glass applications where the goal is not to form ceramic solder.

[0026] In addition, the fusible glass according to an embodiment of the present invention can be used to connect joints (Fügepartnern), in particular joints made of or containing metal and / or made of or containing ceramic, in particular for connecting at least one joint made of or containing metal with at least one joint containing ceramic or made of ceramic. In the context of the present invention, a joint is generally understood to be a component to be connected or already connected to another component.

[0027] In the present invention, the fusible glass is designed to contain SiO2, that is, silicate glass. This has the advantage that SiO2 is a well-known glass component and the industrial production of silicate glass is a well-controlled process.

[0028] The fusible glass according to the invention does not contain PbO except for unavoidable traces. This is advantageous from a regulatory point of view, but especially from a health and environmental point of view, since lead and lead-containing compounds and substances are very harmful to many living organisms.

[0029] The linear thermal expansion coefficient α of the fusible glass of the present invention is 20-300 , i.e. the linear thermal expansion coefficient α determined in the temperature range of 20°C to 300°C 20-300At least 8.0*10 -6 / K, preferably at least 9.0*10 -6 / K, preferably at least 10.0*10 -6 / K, wherein the upper limit of the linear thermal expansion coefficient is preferably at most 17*10 -6 / K. The upper limit of the thermal expansion coefficient may in particular be at most 14*10 -6 / K, preferably at most 12*10 -6 / K. In particular, the linear thermal expansion coefficient may be at least 9*10 -6 / K to up to 14*10 -6 / K, for example, at least 10*10 -6 / K to 14*10 -6 / K. The advantage is that this enables a tight connection of a joint couple, for example, consisting of metal or containing a metal material (for example, an alloy of one or more metals or a metal-ceramic composite). Compared to silicate glass, metals or metal materials generally have a very high linear thermal expansion coefficient. If the linear thermal expansion coefficients of the fusible glass and the material to be connected and / or sealed differ too much from each other, during the use of the sealing and / or joining parts, the glass component may crack and / or the glass component may at least partially detach from the joint couple. This situation can be avoided if the linear thermal expansion coefficients of the fusible glass and the material to be connected and / or sealed are as equal as possible. Therefore, it is also advantageous if the linear thermal expansion coefficient is not too large, because in this way, a sealed connection can be formed between the metal material and the ceramic material, preferably even an airtight connection or a vacuum-tight connection, or the fusible glass can also be used to connect ceramic materials to each other. By clearly selecting the exact composition of the fusible glass within the composition range mentioned within the scope of the present invention, it is possible to achieve an optimal match between the thermal expansion coefficient of the fusible glass and the thermal expansion coefficient of the joint couple to be connected. It should be noted here that the thermal expansion coefficients of many metals are 20*10 -6 / K or higher, while the thermal expansion coefficient of ceramics is usually less than 10*10 -6 / K, usually 7*10 -6 / K. Therefore, the fusible glass used to connect metal and ceramic should have a thermal expansion coefficient that matches both of these thermal expansion coefficients, especially when the glass is melted in a metal shell. Such a metal shell generally contracts strongly during the cooling process after the melting process. Therefore, the fusible glass must also contract strongly to prevent cracks from forming, but not too much to avoid damaging the ceramic surrounded by the fusible glass. In addition, the fusible glass must fully wet the metal surface and the ceramic surface during the melting or melting process to prevent the formation of air gaps.

[0030] The fusible glass contains less than 2 wt % of Al2O3. Al2O3 is a well-known network former, which is added in particular to alkali-containing silicate glasses. This is because the addition of Al2O3 reduces the number of interfacial oxygen, which can be beneficial for certain applications of process glass. However, too high an Al2O3 content reduces the chemical resistance of the resulting glass, in particular the acid resistance. Therefore, according to the present invention, the Al2O3 content of the fusible glass is advantageously limited and is not more than 2 wt %, preferably not more than 1 wt %. According to a particularly preferred embodiment, the fusible glass does not contain Al2O3 except for unavoidable traces. Unavoidable traces of Al2O3 are impurities related to production technology and are at most 3000 ppm by weight. This advantageously enables excellent property stability of the fusible glass under conditions of use. Preferably, these unavoidable traces can also be lower, for example at most 500 ppm by weight.

[0031] The dielectric constant ε of the fusible glass r Preferably it is at least 7.10 and at most 7.80. This is particularly advantageous for certain sensor applications, especially pressure sensors.

[0032] In particular in the case of certain pressure sensors, it may also be advantageous if the glass material (e.g. fusible glass) contained in the sensor has a good temperature-time stability of the dielectric constant. Here, the dielectric constant stability can be determined by comparing the capacitance containing the corresponding glass as dielectric in the initial state (C0) with the capacitance after a certain load (C), for example by the ratio of these capacitances:

[0033]

[0034] Preferably, the dielectric constant is imparted with a good stability if the ratio value is less than 2, preferably less than 1.5, particularly preferably less than 1.2, determined under temperature-time loading at 85° C. for 40 hours and / or 600 hours.

[0035] According to a certain embodiment, the fusible glass has a dielectric constant stability determined by the following ratio:

[0036]

[0037] Where C0 is the capacitance in the initial state,

[0038] C is the capacitance after heat load,

[0039] In this case, the ratio is preferably less than 2, preferably less than 1.5, particularly preferably less than 1.2, determined under a temperature-time load of 85° C. for 40 hours and / or 600 hours.

[0040] Within the scope of the present invention, the following definitions apply:

[0041] The unavoidable traces of element oxides in the fusible glass are impurities related to production technology, for example, impurities caused by the purity of the raw materials used. Therefore, frequently occurring elements (such as aluminum) usually have a higher impurity content than rarely occurring elements (such as lead). The content of PbO in the unavoidable traces in the fusible glass is less than 500 ppm by weight.

[0042] When measured at a heating rate of 5 K / min, the transition temperature (or glass transition temperature) T is determined by the intersection of the tangent lines on the two branches of the expansion curve. g This corresponds to a measurement according to ISO 7884-8 or DIN 52324.

[0043] Within the scope of the present invention, the terms "network modifier" and "network former" are understood and used in the sense of a network hypothesis according to Zachariasen's rule.

[0044] In the context of the present invention, the linear thermal expansion coefficient α or simply the thermal expansion coefficient (also known as CTE) is given in the range of 20°C to 300°C, unless otherwise specified. In the context of the present invention, the terms α and α 20-300 Used as a synonym. The specified value is the nominal mean linear thermal expansion coefficient according to ISO 7991, which is determined in static measurements.

[0045] In the sense of the present invention, the coefficient of thermal expansion (CTE) describes the change in the dimensions of a material when the temperature changes and is based on the material-specific thermal expansion effects. Specifically, reference is made to the coefficient of thermal expansion α defined according to the following formula (I):

[0046]

[0047] In embodiments where the coupling comprises more than one material, the expression "thermal expansion coefficient" relates to the average thermal expansion coefficient of the entire coupling.

[0048] If the bonded element is, for example, a ceramic-metal composite structure consisting of at least one layer of ceramic K2 and at least one layer of metal M2, then the average thermal expansion coefficient The calculation of is as follows:

[0049]

[0050] Among them, the symbols have the following meanings:

[0051] α K2 Thermal expansion coefficient of ceramic K2 [1 / K];

[0052] α M2Thermal expansion coefficient of metal M2 [1 / K];

[0053] E K2 E modulus of ceramic K2 [GPa];

[0054] E M2 E modulus of metal M2 [GPa];

[0055] d K2 Layer thickness of ceramic K2 [m];

[0056] d M2 Layer thickness of metal M2 [m].

[0057] The softening point (SP) is understood to be the glass viscosity of 10 7.6 Temperature at dPas.

[0058] According to a certain embodiment, the fusible glass contains at least 45 wt % SiO2. SiO2 is a well-known network former in glass. The highest possible SiO2 content in the fusible glass is also beneficial to support its chemical stability. Therefore, preferably, the SiO2 content of the fusible glass is at least 50 wt %, preferably at least 51 wt %. However, a high SiO2 content in the fusible glass may be disadvantageous because a too high SiO2 content leads to a high melting temperature and / or softening temperature. A too high SiO2 content also leads to a low linear thermal expansion coefficient. Therefore, it is advantageous to limit the SiO2 content of the fusible glass. Preferably, the fusible glass contains SiO2 of at most 75 wt %, preferably at most 65 wt %, particularly preferably at most 63 wt %, and particularly preferably at most 62 wt %. The SiO2 content of the fusible glass can be, for example, at least 45wt% to at most 75wt%, or at least 50wt% to at most 65wt%, or at least 51wt% to at most 62wt%, or at least 50wt% to at most 63wt%, for example at least 51wt% to at most 56wt%, or at least 50wt% to at most 72wt%, for example at least 58wt% to at most 63wt%.

[0059] According to another embodiment, the fusible glass contains at least 2 wt% of B2O3. B2O3 is also a well-known component in glass and belongs to one of the network formers. The lowest content of B2O3 is advantageous because the B2O3 content in the glass reduces the melting temperature. Preferably, the B2O3 contained in the fusible glass is at least 5 wt%, preferably at least 7 wt%, particularly preferably at least 8 wt%, and particularly preferably at least 13 wt%. However, too high a B2O3 content may have an adverse effect on chemical stability, especially hydrolysis resistance. Therefore, it is preferred to limit the B2O3 content in the fusible glass. According to a certain embodiment, the B2O3 contained in the fusible glass is at most 20 wt%, preferably at most 18 wt%, and particularly preferably at most 17 wt%. The advantageous range of the B2O3 content may be 5 wt% to 18 wt%, or 8 wt% to 17 wt%, or 7 wt% to 11 wt%, or 13 wt% to 18 wt%.

[0060] According to another embodiment, the total content of alkali metal oxides R2O in the fusible glass is at least 10 wt%. Alkali metal oxides are so-called network modifiers. It is advantageous for the fusible glass to contain alkali metal oxides, because they reduce the melting temperature and lead to an increase in the linear thermal expansion coefficient. The network modifiers lead to an increase in the number of interface oxygens in the glass network, which is also conducive to obtaining a sufficiently high dielectric constant, preferably at least 7.1, preferably determined at a measurement frequency of 1 MHz and a temperature of 25°C. Therefore, preferably, the total content of alkali metal oxides R2O in the fusible glass is at least 17 wt%, preferably at least 13 wt%, more preferably at least 14 wt%, still more preferably at least 15 wt%, particularly preferably at least 16 wt%, and most preferably at least 17 wt%. However, according to the present invention, the content of alkali metal oxides in the fusible glass should not be too high, because they reduce the chemical resistance. In particular, a too high content of alkali metal oxides may result in the dielectric properties of the fusible glass (such as the dielectric constant) being less stable in an environment with increased air humidity. Therefore, according to a certain embodiment, the total content of alkali metal oxides in the fusible glass is limited and is at most 40 wt%, preferably at most 35 wt%, preferably at most 34 wt%, more preferably at most 30 wt%, particularly preferably at most 26 wt%, and particularly preferably at most 24 wt%. The total content of alkali metal oxides R2O in the fusible glass can advantageously range from 15 wt% to 35 wt%, or from at least 13 wt% to at most 30 wt%, or from at least 14 wt% to at most 26 wt%, or from at least 16 wt% to at most 24 wt%, or from at least 17 wt% to at most 34 wt%.

[0061] A particularly critical component is the alkali metal oxide Na2O. The fusible glass may comprise Na2O as an optional component, wherein the content of Na2O in the fusible glass is at most 10 wt %, preferably at most 5 wt %, preferably at most 0.5 wt %, wherein the fusible glass contains no Na2O except for unavoidable traces. Na2O is a well-known glass component and is often used in glass due to its good availability and the resulting cost advantage over other glass components. However, Na2O is not conducive to the application areas proposed herein, because sodium ions are particularly mobile in the glass network, thereby significantly reducing the stability of the glass (such as fusible glass). In particular, sodium ions in the glass network are most mobile when an electric field is applied and / or when the temperature rises, so that lithium ions are not favorable if, for example, a good stability (for example of the dielectric constant) is to be achieved. Sodium ions can also be particularly easy to precipitate from the glass material. In order to achieve an excellent stability of the properties of the fusible glass, it is advantageous to limit the Na2O content in the fusible glass. This content is preferably at most 500 ppm by weight. In other words, the fusible glass according to a certain embodiment does not contain Na2O except for unavoidable trace amounts.

[0062] According to another embodiment, the fusible glass comprises Li2O. According to one embodiment, the fusible glass comprises between 0 wt% and preferably up to 10 wt% Li2O. As an alkali metal oxide, Li2O is a network modifier. Therefore, the Li2O content in the fusible glass is conducive to obtaining a low softening temperature. Li2O is a preferred component of the fusible glass according to an embodiment of the present invention, because the lithium ion field strength is very high and therefore, despite its small size, it is generally more firmly bound to the glass network than, for example, sodium ions. According to some embodiments, the fusible glass may contain at least 1 wt% Li2O, preferably at least 3 wt%. However, the Li2O content in the fusible glass must not be too high. On the one hand, Li2O is a relatively expensive component compared to other components. On the other hand, it is known that Li2O as a component in glass can also lead to glass segregation and / or crystallization. In addition, lithium ions bind to interfacial oxygen relatively strongly due to their high field strength, which is unfavorable for the polarizability of interfacial oxygen generated by introducing Li2O into the glass network and reduces the dielectric constant. Preferably, according to some embodiments, the fusible glass comprises Li2O, namely at most 10 wt%, preferably at most 5 wt%. According to another embodiment, the fusible glass comprises at most 1 wt% Li2O. Even more preferably, the fusible glass contains no Li2O except for unavoidable traces. Unavoidable traces of Li2O are Li2O contents of at most 500 ppm by weight. According to some embodiments, a preferred range of Li2O contents may be at least 1 wt% to at most 10 wt% Li2O by weight, for example at least 3 wt% to at most 5 wt%.

[0063] According to another embodiment, the fusible glass contains at least 5 wt% of K2O. As an alkali metal oxide, K2O serves as a component for reducing the softening temperature. Therefore, the K2O content should not be less than 5 wt%, otherwise the softening temperature cannot be sufficiently reduced. The K2O content of the fusible glass is preferably at least 8 wt%, preferably at least 10 wt% of K2O, more preferably at least 12 wt% of K2O, particularly preferably 14 wt% of K2O, and particularly preferably at least 15 wt% of K2O. Potassium ions also have a relatively lower field strength than lithium ions and sodium ions. This is conducive to achieving a sufficiently high dielectric constant, preferably determined at a measuring frequency of 1 MHz and a temperature of 25°C, which is preferably at least 7.1, because potassium ions have less interfacial oxygen bonding due to their extremely low field strength compared to lithium ions and / or sodium ions. However, the K2O content must not be too high, because as an alkali metal oxide, K2O is also a mobile component in the glass network, and if the content is too high, it may lead to poor chemical resistance of the fusible glass. Therefore, the K2O content of the fusible glass is preferably limited, according to a certain embodiment, to a content of at most 40 wt% K2O. Preferably, the K2O content of the fusible glass is at most 35 wt%, particularly preferably at most 34 wt%, especially preferably at most 20 wt%, and most preferably at most 18 wt%. Potassium ions are larger than sodium ions and therefore have less mobility in the glass network than sodium ions. The preferred range of the K2O content of the fusible glass may be at least 10 wt% to at most 35 wt%, such as at least 15 wt% to at most 35 wt%, especially 15 wt% to 20 wt%, or at least 8 wt% to at most 34 wt%, especially 14 wt% to at most 34 wt%, or at least 12 wt% to at most 20 wt%, such as at least 15 wt% to at most 18 wt%.

[0064] In order to ensure adequate temperature-time stability of the fusible glass, in particular its physical and chemical properties, such as the dielectric constant, the content of so-called "mobile" ions in the glass network should be as low as possible. However, such mobile ions are precisely those ions which are necessary as components in the form of so-called network modifiers, such as alkali metal oxides and / or alkaline earth metal oxides, in order to lower the glass temperature and thus the melting temperature, in particular if PbO is omitted as a glass component. It has proven to be advantageous to add, apart from unavoidable impurities, no more than two different alkali metal oxides as components. Advantageously, therefore, according to a certain embodiment, the fusible glass comprises only two different alkali metal oxides as components, preferably Li2O and K2O.

[0065] This is advantageous, since alkali metals are not only detrimental to good glass resistance, but it must also be taken into account that alkali metals are highly aggressive in contact with ceramics and may at least partially decompose or dissolve the ceramics. Therefore, according to a certain embodiment, the alkali metal oxide content in the fusible glass is limited so that the total content of the fusible glass does not exceed at most 24% by weight and the fusible glass contains only two alkali metal oxides as components, in addition to unavoidable impurities of other alkali metal oxides. Within the scope of the present invention, the fusible glass "comprising oxides as components" or the fusible glass "adding oxides as components" is to be understood as intentional addition and not just inclusion of the corresponding oxides in the fusible glass as eventual unavoidable impurities. Unavoidable impurities of alkali metal oxides are generally in the range of up to 500 ppm per alkali metal oxide (by weight).

[0066] Surprisingly, it has been found that K2O is particularly advantageous as a component of fusible glasses. Based on the results of precipitation and cleaning tests, it can be observed that potassium ions are not uniformly precipitated in comparison with sodium ions. Instead, potassium ions are enriched in the near-surface region. It is then believed that this potassium ion enrichment represents a diffusion barrier for further precipitation. In fusible glasses according to embodiments of the present invention, the mobility of the inherent mobile ions of alkali metals and / or alkaline earth metals may be at least limited, which in turn unexpectedly leads to the surprisingly good stability observed for fusible glasses according to embodiments of the present invention. This potassium enrichment may also explain the unexpectedly low corrosivity exhibited by fusible glasses according to embodiments of the present invention when in contact with ceramics.

[0067] The stability of the fusible glass according to the embodiment of the present invention showing the above-mentioned advantageous properties despite the presence of potassium oxide and lithium oxide in the fusible glass is also surprising, because silicate glasses containing lithium oxide and / or potassium oxide, especially borosilicate glasses containing lithium oxide and / or potassium oxide, have a strong tendency to segregate, and sometimes even segregate to form a permeable structure (sometimes also referred to as metastable segregation). Such a permeable structure may be particularly disadvantageous when the segregation occurs in a high-content SiO2 phase that is soluble (e.g., highly rich in boron and alkali) and chemically resistant. Therefore, the fusible glass according to the present invention apparently seems to have formed such a permeable structure, but the excellent resistance currently shown is quite unexpected. Obviously, the fusible glass according to the embodiment of the present invention stably prevents segregation (also often referred to as "metastable segregation") when the permeable structure is formed.

[0068] In inherently segregated glass systems, this stability is usually achieved by adding Al2O3. However, the fusible glass according to embodiments of the present invention contains only a small amount of Al2O3. 3,Preferably, no Al2O3 is contained except for unavoidable traces. Thus, against this background, a high chemical stability of the fusible glass according to embodiments of the invention is surprisingly observed.

[0069] Furthermore, the production process of the fusible glass according to embodiments of the present invention is also problem-free. In particular, the undesired crystallization that is often observed in segregated glass systems does not occur. Furthermore, the fusible glass according to embodiments of the present invention can be further heat treated after melting, in particular pressed, without, for example, macroscopically visible haze forming in the fusible glass.

[0070] The inventors have deduced that microphase separation may occur in the system observed here, for example in the form of droplet segregation and / or so-called clusters, i.e., random aggregations of individual glass components which deviate from the statistical distribution and which usually have only a very small spatial extent of at most a few micrometers in diameter, mostly less than 1 micrometer or even only a few hundred nanometers or less, and are therefore not or barely recognizable as segregations optically and / or chemically. Such clusters can be understood as "cluster-like aggregations" in the sense of Hartleif and Dietzel. However, such clusters cannot be detected in fusible glasses according to embodiments of the present invention at present. The reason for the difficulty in detection is that the observed stability of the properties of fusible glasses according to embodiments of the present invention indicates that the properties of the "clusters" or "droplets" differ only slightly from the surrounding glass matrix, for example they have very similar chemical resistance.

[0071] Another component of the fusible glass is preferably CaO. According to one embodiment, the fusible glass contains between 0 wt% and preferably up to 15 wt% CaO. CaO, as an alkaline earth metal oxide, is also a network modifier and is therefore also suitable for reducing the softening temperature. Therefore, according to a certain embodiment, the CaO content of the fusible glass is at least 1 wt%, preferably at least 5 wt%, preferably at least 5 wt%, particularly preferably 10 wt%, especially preferably at least 11 wt%, and most preferably at least 12 wt%. According to ion exchange experiments, CaO as a component can significantly reduce the mobility of alkali metal ions, so it can be used in the fusible glass according to the embodiment of the present invention to stabilize the dielectric constant. However, the CaO content may also have disadvantages because CaO can also cause segregation and / or crystallization in the glass. According to another embodiment, it is advantageous that the CaO content of the fusible glass is not too high, for example, at most 15 wt%, or only at most 14 wt%, or even only 13 wt%. In other feasible embodiments, the CaO content is even lower, for example, at most 7 wt%, or even only 1 wt%. In particular, according to a certain embodiment, the fusible glass may also be free of CaO except for unavoidable traces. Here, the unavoidable traces of CaO in the fusible glass may be at most 500 ppm by weight. The preferred range of the CaO content of the fusible glass may be from 0 wt% CaO to at most 15 wt% CaO, preferably at most 7 wt% CaO, preferably at most 13 wt% CaO, to at most 1 wt% CaO, or at least 1 wt% CaO to at most 15 wt% CaO, for example at least 5 wt% to at most 15 wt%, preferably at least 10 wt% CaO to at most 15 wt% CaO, particularly preferably at least 11 wt% CaO to at most 14 wt% CaO, and particularly preferably at least 12 wt% CaO to 13 wt% CaO.

[0072] Another optional component of the fusible glass is BaO. BaO, as an alkaline earth metal oxide, is also a network modifier and is therefore suitable for advantageously helping to obtain a lower softening temperature. Therefore, according to some embodiments, the fusible glass may contain up to 16 wt% of BaO. However, preferably, the BaO content of the fusible glass is also limited, because BaO may especially cause segregation and / or crystallization. In addition, BaO also increases the density of the fusible glass, which leads to a higher weight and is therefore not conducive to application. Therefore, preferably, the BaO content in the glass is at most 10 wt%, preferably at most 5 wt%, and particularly preferably at most 1 wt%. It is particularly preferred that the fusible glass does not contain BaO except for unavoidable traces. Here, the unavoidable trace amount of BaO is at most 500 ppm.

[0073] ZnO is a further optional component of the fusible glass. According to one embodiment, the fusible glass contains between 0 wt % and preferably up to 8 wt % ZnO. ZnO is a subgroup element and acts here like alkaline earth metal oxides as a network modifier in the glass network and thus also contributes to the lower softening temperature in the present invention. According to a certain embodiment, the ZnO content of the fusible glass is preferably at least 2 wt %. However, the ZnO content of the fusible glass should not be too high and according to a certain embodiment, its content is at most 8 wt %, preferably at most 5 wt %, particularly preferably at most 4.5 wt %, especially preferably at most 4 wt %, whereby these embodiments may also have lower contents, for example only at most 1 wt %. It is particularly advantageous to reduce and preferably limit the content in the fusible glass according to embodiments of the present invention, because zinc silicate glasses may also tend to segregate. According to another embodiment, the fusible glass contains no ZnO except for unavoidable traces. The content of unavoidable traces of ZnO is at most 500 ppm. The preferred range of the ZnO content may be at least 2 wt% to at most 4.5 wt%, preferably at least 2 wt% to at most 4 wt%.

[0074] Another optional component of the fusible glass is fluorine F, especially as fluoride ion or in the form of fluoride ion F. - In the context of the present invention, the fluorine content in the fusible glass is discussed below, and the fluoride F in the fusible glass is also considered. - content. Fluorine is a component that acts as a flux in the glass and therefore reduces the softening temperature. According to a certain embodiment, the fusible glass preferably contains at least 0.1wt% fluorine, preferably at least 0.5wt% fluorine. According to a certain embodiment, the fusible glass even contains at least 5wt% fluorine. However, if the F content is too high, the corrosion of the molten pool is aggravated, so the fluorine content in the fusible glass is preferably limited. The fluorine contained in the fusible glass is at most 10wt%, preferably at most 8wt%. It is also conceivable to further limit the fluorine content of the fusible glass, for example, the fusible glass contains at most 2wt% fluorine, or even at most 1.5wt% fluorine. The preferred range of fluorine content may be at least 0.5wt% to at most 8wt%, or at least 0.1wt% to at most 2wt%, or at least 0.5wt% to at most 1.5wt%, or at least 5wt% to at most 8wt%.

[0075] It has also proven to be advantageous that in the fusible glass according to an embodiment of the invention, at most two migrating components are used, namely alkaline earth metal oxides and alkali metal oxides. Therefore, the content of alkaline earth metal oxides or oxides that similarly act as alkaline earth metal oxides in the glass network in the fusible glass according to an embodiment of the invention is preferably limited in type and, alternatively or additionally, in quantity. Within the scope of the present invention, an oxide that acts as an alkaline earth metal oxide in the glass network is particularly understood to be ZnO, usually an RO-type oxide. Preferably, the fusible glass according to an embodiment of the invention contains only two alkaline earth metal oxides or oxides that act as alkaline earth metal oxides, particularly preferably calcium oxide and zinc oxide, as components. More preferably, according to a certain embodiment, the sum of the contents of alkaline earth metal oxides or oxides that act as alkaline earth metal oxides is at least 4 wt % and at most 17 wt %, wherein according to one embodiment, the sum of the contents of CaO and ZnO in the fusible glass is particularly preferably at least 4 wt % and at most 17 wt %.

[0076] The fusible glass according to an embodiment of the invention is particularly suitable in that the initially produced rod can be pressed again at least once, and the pressed product can then be used, for example, in a so-called reflow process for crack-free melting of, for example, a wire.

[0077] According to another embodiment, the glass transition temperature T g The temperature is 400°C to 550°C, preferably 450°C to 500°C.

[0078] According to a certain embodiment, the fusible glass comprises the following components (in terms of oxide wt%):

[0079] SiO2 45-75, preferably 50-65, particularly preferably 51-62,

[0080] Al2O3 0–2, preferably free of Al2O except for unavoidable trace amounts 3,

[0081] B2O3 2-20, preferably 5-18, particularly preferably 8-17,

[0082] Li2O 0–10, preferably 0–5,

[0083] Na2O 0-10, preferably free of Na2O except for unavoidable trace amounts,

[0084] K2O 5-40, preferably 8-34, particularly preferably 14-34,

[0085] CaO 0–15, preferably 0–13,

[0086] BaO 0-16, preferably 0-10, particularly preferably free of BaO except for unavoidable traces,

[0087] ZnO 0–8, preferably 0–5,

[0088] F 0–10, preferably 0.5–8,

[0089] wherein the sum of alkali metal oxides ΣR2O is at least 10 wt% to at most 40 wt%, preferably at least 15 wt% to at most 35 wt%,

[0090] The fusible glass contains no Na2O and PbO except for unavoidable traces, wherein the unavoidable traces of Na2O and PbO are each at most 500 ppm by weight, wherein the fusible glass may also contain other minor components and / or traces, for example in the form of fining agents, wherein the sum of the minor components and / or traces is preferably less than 2 wt%.

[0091] Therefore, the glass according to the present invention may contain a small amount of conventional fining agents. The total amount of the added fining agent is preferably at most 1.0 wt%, more preferably at most 0.5 wt%. The glass according to the present invention may contain at least one of the following components as a fining agent (by wt%):

[0092]

[0093] For example, zinc peroxide, lithium peroxide and / or alkaline earth metal peroxides can be used as the inorganic peroxide.

[0094] In an advantageous embodiment, the glass according to the invention is refined with AS 2 O 3 .

[0095] In a further advantageous embodiment of the invention, the glass contains no As 2 O 3 , since this component is considered to be problematic for environmental reasons.

[0096] It has been found that a particularly advantageous composition range of the fusible glass is achieved in this way.

[0097] In particular, the fusible glass having such a composition contains relatively low-cost raw materials in addition to Li2O and can ensure good supply safety.

[0098] This composition also has advantages with regard to the stability of the dielectric properties. Ultimately, in order to ensure that the glass properties, in particular the dielectric properties, such as the dielectric constant, have sufficient temperature-time stability, the content of "migrant" ions in the fusible glass must be reduced overall, i.e. preferably both in type and in number. On the other hand, a sufficient amount of such migrating ions, in particular so-called network modifiers, must be present in order to achieve the lowest possible melting temperature. However, a high content of network modifiers in a glass such as a fusible glass generally leads to a low T g and a high linear thermal expansion coefficient. However, in the present invention, the glass transition temperature T g The temperature should preferably be as low as possible, particularly advantageously 500°C or lower, but at the same time the coefficient of thermal expansion is also limited, preferably below 14*10 -6 / K, particularly preferably less than 13*10 -6 / K, particularly preferably less than 11*10 -6 / K, for example 10.5*10 -6 K or even less. Therefore, in the present invention, a certain content of mobile ions is required, but not too much, and not too much. It has been proven that a good compromise is achieved by the composition of the fusible glass as described above. In this way, in particular, a low glass transition temperature can be obtained, while the linear thermal expansion coefficient is not too high, and the glass properties of the fusible glass, especially its dielectric properties, have good stability.

[0099] Examples

[0100] The present invention is described in detail below with reference to examples. In the examples, if the total content is less than 100 wt%, it may be due to common measurement-related errors and / or possible trace amounts and / or rounding errors.

[0101] The advantageous composition of the fusible glass according to the invention is given by the following composition range (in terms of oxide wt %):

[0102] SiO2 45-75, preferably 50-65, particularly preferably 51-62,

[0103] Al2O3 0–2, preferably free of Al2O except for unavoidable trace amounts 3,

[0104] B2O3 2-20, preferably 5-18, particularly preferably 8-17,

[0105] Li2O 0–10, preferably 0–5,

[0106] Na2O 0-10, preferably free of Na2O except for unavoidable trace amounts,

[0107] K2O 5-40, preferably 8-34, particularly preferably 14-34,

[0108] CaO 0–15, preferably 0–13,

[0109] BaO 0-16, preferably 0-10, particularly preferably free of BaO except for unavoidable traces,

[0110] ZnO 0–8, preferably 0–5,

[0111] F 0–10, preferably 0.5–8,

[0112] The total sum of alkali metal oxides ΣR2O is at least 10 wt% to at most 40 wt%, preferably at least 15 wt% to at most 35 wt%.

[0113] Another advantageous composition of the fusible glass according to the invention is given by the following composition range (in terms of oxide wt %):

[0114] SiO2 50–63, preferably 51–56,

[0115] Al2O3 0–2, preferably free of Al2O except for unavoidable trace amounts 3,

[0116] B2O3 5–18, preferably 7–11,

[0117] Li2O 1–10, preferably 3–5,

[0118] Na2O 0-10, preferably 0-0.5, particularly preferably free of Na2O except for unavoidable traces,

[0119] K2O 12–20, preferably 15–18,

[0120] CaO 1-15, preferably 5-15, more preferably 10-15, particularly preferably 11-14, and especially preferably 12-13,

[0121] BaO 0–5, preferably 0–1,

[0122] ZnO 0-5, preferably 2-4.5, particularly preferably 2-4,

[0123] F 0-5, preferably 0.1-2, particularly preferably 0.5-1.5,

[0124] The total ΣR2O of the alkali metal oxides is at least 13 wt% to at most 30 wt%, preferably at least 14 wt% to at most 26 wt%, and particularly preferably at least 16 wt% to at most 24 wt%.

[0125] With fusible glass having a composition within the above composition range, a dielectric constant ε of at least 7.40 to at most 7.80, preferably determined at a measuring frequency of 1 MHz and a temperature of 25° C., can be achieved. r .

[0126] For the fusible glass having a composition within the above composition range, the glass transition temperature T g It is preferably 400°C to 550°C, more preferably 450°C to 500°C.

[0127] Example 1:

[0128] According to a certain embodiment, the fusible glass comprises the following components (in wt% of oxides):

[0129]

[0130] With the fusible glass composition according to Example 1, the following properties are achieved:

[0131]

[0132] In the context of the present invention, the softening temperature is a glass (here, the fusible glass according to the embodiment) with a viscosity of 10 7.6 dPas, the working point is the glass (here, the fusible glass according to the embodiment) with a viscosity of 10 -4 Temperature in dPas.

[0133] Example 2:

[0134] According to another embodiment, the fusible glass comprises the following components (in wt% of oxides):

[0135]

[0136]

[0137] With the fusible glass composition according to Example 2, the following properties are achieved:

[0138]

[0139] Example 3:

[0140] According to yet another embodiment, the fusible glass comprises the following components (in wt% of oxides):

[0141]

[0142] With the fusible glass composition according to Example 3, the following properties are achieved:

[0143]

[0144] Here, the fusible glass according to Examples 1 to 3 preferably contains no Na2O and PbO except for unavoidable traces, wherein the unavoidable traces of Na2O and PbO are in each case at most 500 ppm by weight, wherein the fusible glass may contain further minor components and / or traces, for example in the form of fining agents, wherein the sum of these minor components and / or traces is preferably less than 2 wt.%.

[0145] A further advantageous composition of the fusible glass according to the invention is given by the following composition range (in terms of oxide wt %):

[0146] SiO2 50–72, preferably 58–63,

[0147] Al2O3 0–2, preferably free of Al2O except for unavoidable trace amounts 3,

[0148] B2O3 2–20, preferably 13–18,

[0149] Li2O 0-5, preferably 0-1, particularly preferably containing no Li2O except for unavoidable traces,

[0150] Na2O 0-10, preferably 0-5, particularly preferably free of Na2O except for unavoidable traces,

[0151] K2O 10-35, preferably 15-35, particularly preferably 15-20,

[0152] CaO 0-7, preferably 0-1, particularly preferably free of CaO except for unavoidable traces,

[0153] BaO 0-16, more preferably 0-5, particularly preferably 0-1, particularly preferably free of BaO except for unavoidable traces,

[0154] ZnO 0-5, preferably 0-1, particularly preferably free of ZnO except for unavoidable traces,

[0155] F 0–8, preferably 5–8.

[0156] wherein the sum of alkali metal oxides ΣR2O is at least 15 wt% to at most 35 wt%, preferably at least 17 wt% to at most 34 wt%,

[0157] With the fusible glass having a composition within the above composition range, a dielectric constant εr of at least 7.10 to at most 7.80, preferably determined at a measuring frequency of 1 MHz and a temperature of 25° C., can be achieved.

[0158] For the fusible glass having a composition within the above composition range, the glass transition temperature T g It is preferably 400°C to 550°C.

[0159] Example 4:

[0160] According to another embodiment, the fusible glass comprises the following components (in wt% of oxides):

[0161]

[0162]

[0163] With the fusible glass composition according to Example 2, the following properties are achieved:

[0164] BRIEF DESCRIPTION OF THE DRAWINGS

[0165] The present invention is described in detail below in conjunction with the accompanying drawings.

[0166] Figure 1 ToF-SIMS images of two potassium-containing glasses are shown to illustrate the formation of potassium enrichment. DETAILED DESCRIPTION

[0167] Figure 1 The concentration curves of certain ions determined by means of ToF-SIMS in a potassium-containing glass are shown to illustrate the potassium enrichment in the surface layer of the glass.

[0168] Part a) shows a first ToF-SIMS image of a potassium-containing glass in a ground and polished state. The Y-axis represents the intensity of the measured signal in arbitrary units wE, and the x-axis represents the sputtering time in seconds, wherein a longer sputtering time indicates a deeper penetration into the surface of the sample to be tested (here, potassium-containing glass).

[0169] Potassium ions K are shown and labeled accordingly. + , Boron ion B 3+ 、Barium ion Ba 2+ (for 137 Ba 2+ ), aluminum ion Al 3+ 、Sodium ion Na + and lithium ion Li + Concentration curves 1, 2, 3, 4, 5 and 6 on a glass surface.

[0170] In contrast, Figure 1 Part b) shows the respective concentration curves after cleaning.

[0171] The sample surface of part a) was indeed also polished and thus at least slightly cleaned. Figure 1 The sample in part b) of FIG. 1 was subjected to a corresponding surface cleaning, such as is performed during the production of optical elements such as lenses. The sample surface on which the ToF-SIMS image of part b) is based was therefore exposed to moisture in the form of an aqueous cleaning solution for a long period of time.

[0172] It can be seen that for Figure 1 For the glass considered in , after such a cleaning process, there is an enrichment of potassium in the near-surface layer of 10, which corresponds to a sputtering time of about 700 seconds.

[0173] The inventors believe that in fusible glasses according to embodiments of the present invention, the ability of potassium to form such an enriched layer upon contact with the glass surface can have a surprisingly positive effect on the stability of the glass properties, especially the dielectric properties, even under temperature loads. In fact, the formation of such a potassium-rich layer can prevent the migration of other ions and / or stabilize the polarizability of the glass network.

[0174] Reference numerals list

[0175] 1 Potassium concentration curve

[0176] 11 Potassium Enrichment

[0177] 2 Boron concentration curve

[0178] 3 137 Ba concentration curve

[0179] 4 Aluminum concentration curve

[0180] 5 Sodium concentration curve

[0181] 6 Lithium concentration curve

Claims

1. A sealing glass comprising: at least 45 wt% SiO2; Less than 2wt% Al2O3; Not more than 5 wt% Na2O; Contains no PbO except for unavoidable trace amounts; Greater than 0 wt% Li2O; and at least 5 wt% K2O; in, The linear thermal expansion coefficient of the sealing glass is α 20-300 Greater than 10*10 -6 / K; The dielectric constant ε of the sealing glass is determined at a measurement frequency of 1 MHz and a temperature of 25°C. r is at least 7.10 and at most 7.80, Among them, the glass transition temperature T g 400℃ to 550℃.

2. The sealing glass according to claim 1, wherein: The glass transition temperature T g 450℃ to 500℃.

3. The sealing glass according to claim 1, wherein: The sealing glass contains at least 45 wt % and at most 75 wt % SiO 2 .

4. The sealing glass according to claim 1, wherein: The total content of alkali metal oxides R2O in the sealing glass is at least 10 wt% and at most 40 wt%, wherein the content of Na2O in the sealing glass is at most 500 ppm. The sealing glass according to claim 1 , comprising up to 10 wt % of Li 2 O. The sealing glass according to claim 1 , comprising at least 5 wt % and at most 40 wt % of K 2 O.

7. The sealing glass according to claim 1, wherein: The sealing glass comprises two different alkaline earth metal oxides. 8 . The sealing glass according to claim 1 , comprising 0 wt % to at most 8 wt % ZnO.

9. The sealing glass according to claim 1, having a dielectric constant stability determined by the following ratio: in, C0 is the capacitance in the initial state, C is the capacitance after heat load, Therein, the ratio is less than 2, determined under a heat load of 85° C.

10. The sealing glass according to claim 9, wherein: The heat load is maintained between 40 hours and 600 hours.

11. The sealing glass according to claim 9, wherein: The ratio is less than 1.

2.

12. The sealing glass according to claim 1, comprising the following components, calculated by oxide wt %: in, The sum of alkali metal oxides ΣR2O is at least 10 wt% and at most 40 wt%, Therein, Na2O and PbO are both at most 500 ppm by weight.

13. The sealing glass according to claim 1, comprising the following components, calculated by oxide wt %: in, The sum of alkali metal oxides ΣR2O is at least 13 wt% and at most 30 wt%, Therein, Na2O and PbO are both at most 500 ppm by weight.

14. The sealing glass according to claim 1, comprising the following components, calculated by oxide wt %: in, The sum of alkali metal oxides ΣR2O is at least 15 wt% and at most 35 wt%, Therein, Na2O and PbO are both at most 500 ppm by weight.

15. A sealing glass comprising: at least 45 wt% SiO2; Less than 2wt% Al2O3; No more than 5 wt% Na2O; and Contains no PbO except for unavoidable trace amounts; in, The linear thermal expansion coefficient of the sealing glass is α 20-300 Greater than 10*10 -6 / K; The dielectric constant ε of the sealing glass is determined at a measurement frequency of 1 MHz and a temperature of 25°C. r is at least 7.10 and at most 7.80, Wherein, the glass transition temperature of the sealing glass is T g 400°C to 550°C; The content of B2O3 is at least 2 wt% and at most 20 wt%.

16. A sealing glass comprising: at least 45 wt% SiO2; Less than 2wt% Al2O3; No more than 5 wt% Na2O; and Contains no PbO except for unavoidable trace amounts; in, The linear thermal expansion coefficient of the sealing glass is α 20-300 Greater than 10*10 -6 / K; The dielectric constant ε of the sealing glass is determined at a measurement frequency of 1 MHz and a temperature of 25°C. r is at least 7.10 and at most 7.80, Wherein, the glass transition temperature of the sealing glass is T g 400°C to 550°C; wherein the content of CaO is greater than 0 wt % to at most 15 wt %; and The content of ZnO is greater than 0 wt % to at most 8 wt %.

17. A sealing glass comprising: at least 45 wt% SiO2; Less than 2wt% Al2O3; Not more than 5 wt% Na2O; A glass network modifier comprising CaO and ZnO; and Contains no PbO except for unavoidable trace amounts; in, The linear thermal expansion coefficient of the sealing glass is α 20-300 Greater than 10*10 -6 / K; The dielectric constant ε of the sealing glass is determined at a measurement frequency of 1 MHz and a temperature of 25°C. r is at least 7.10 and at most 7.80; and Wherein, the glass transition temperature Tg of the sealing glass is 400°C to 550°C.